Impact of the pneumococcal conjugate vaccines on invasive pneumococcal disease in France, 2001–2012. Issue 2 (3rd January 2015) - Lepoutre, A.; Varon, E.; Georges, S.; Dorléans, F.; Janoir, C.; Gutmann, L.; Lévy-Bruhl, D.; the Microbiologists of the Epibac, 1; the ORP Networks, 2
Highlights PCVs coverage increased from 56% in those born in 2004 to 94% in those born in 2008. After PCV7, IPD decreased in children <2 years, but not in older age-groups. After PCV13, IPD declined in children <2 years, and in other non-targeted age-groups. For the whole PCV7 + PCV13 period, IPD declined only in children aged 0–4 years.